2011
DOI: 10.1002/smi.1405
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Model of Source‐specific Interpersonal Conflict in Health Care

Abstract: Nurses work in complex social environments, and conflict may arise with fellow coworkers, their supervisor, physicians or the patients and family they care for. Although much research has documented the negative effects of conflict on nurses, no research to date has examined the comparative effect that conflict from all four sources can have on nurses. The purpose of this study is to test a model of workplace conflict where the negative effect of conflict on nurses will be experienced via emotional exhaustion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 43 publications
(74 reference statements)
2
21
0
1
Order By: Relevance
“…Guidroz et al (2012) found that interpersonal conflicts with doctors, patients, and supervisors influenced nurses’ retention outcomes by increasing their emotional exhaustion. In addition, previous research suggests that coworker psychological aggression is related to somatic symptoms such as headaches (Bowling and Beehr 2006; Hershcovis and Barling 2010).…”
Section: Coworker Psychological Aggressionmentioning
confidence: 99%
“…Guidroz et al (2012) found that interpersonal conflicts with doctors, patients, and supervisors influenced nurses’ retention outcomes by increasing their emotional exhaustion. In addition, previous research suggests that coworker psychological aggression is related to somatic symptoms such as headaches (Bowling and Beehr 2006; Hershcovis and Barling 2010).…”
Section: Coworker Psychological Aggressionmentioning
confidence: 99%
“…Recently, there have been concerns about workplace interpersonal conflict (WIC) and its impact on the healthcare system and the workers [ 6 ]. A variety of individuals, including doctors, nurses, co-workers, managers and administrative workers might have experienced conflicts [ 7 ]. The WICs were also commonly encountered in intensive care units [ 8 ], operating rooms [ 9 ] and emergency rooms [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that in some contexts, nurses come into conflict with other players in the clinic or hospital, such as their managers, other nurses, doctors, patients and patients’ relatives (Guidroz, Wang & Perez 2012 ). Numerous studies around the world have shown robust associations between interpersonal conflict and burnout in various contexts (García-Izquierdo & Ríos-Rísquez 2012 ; Guidroz et al 2012 ; Kitaokai & Masuda 2012 ).…”
Section: Introductionmentioning
confidence: 99%